Cryopreservation of turbot Scophthalmus maximus (L.) sperm: fertilization and hatching rates - Chereguini-Fernández-Maquieira; María del Olvido; García-de-la-Banda, Inés; Herrera, M.; Martínez, C.; Hera-San-Juan, Mariano de-la (Aquaculture Research, 2003)
The present paper assesses the fertilization and hatching rates of an artificial fertilization series (n=1153) using fresh and cryopreserved sperm from 49 specimens of turbot Scophthalmus maximus (L.), carried out to confirm the results of a previous study, with the ultimate aim of transferring these cryo-preservation techniques to commercial hatcheries. No significant differences were found between the fertilization rates of the two groups (fresh and cryopreserved sperm) when their respective fertility rates were >69.2%, which was the case in 75% of all fertilizations. Likewise, no significant differences in hatching rates were found. In order to use the cryopreserved sperm more efficiently, a key concern for commercial use of this technique, we also experimented with a lower sperm:diluent ratio (1:1) than used previously at our centre. We also compared the traditional 0.5-mL straws with 2-mL cryotubes able to contain a higher volume of sperm, finding no significant differences in the resulting fertilization and hatching rates. In conclusion, the use of cryopreservation for turbot sperm presents major advantages for broodstock management in commercial hatcheries. Sí